The Dynamics of the Development of Islamic Education in Southeast Asia - Zurqoni, Zurqoni; Arbain, Muhammad; Fauzan, Umar (Borneo International Journal of Islamic Studies, 2019)
This study illustrates the dynamics of the development of Islamic education in Southeast Asia which includes several states such as Indonesia, Malaysia, Brunei Darussalam, and Southern Thailand which have different and unique features of Islamic education as a characteristic of each country. This research also not only explains the differences in the style of Islamic education but analyzes the various dynamics of development that occur behind the formation of a pattern of Islamic education as the grand design of Islamic education in Southeast Asia. The research methodology used is descriptive qualitative data collection techniques in the form of observation, interviews, and documentation. The results found a variety of features or models that became the grand design of Islamic education in each country, namely: (1) Indonesia has a grand design of Islamic education with patterns (2-6-3-3-4); RA 2 years, MI 6 years, MTs 3 years and MA 3 years, and PT 4 years; (2) Malaysia has a grand design with patterns: (4 / 6-7 / 12-3-2-1 / 2); PPD 4-6 years, PD 7-12 years, PMP 3 years, PMA 3 years, PP-PMA 1-2 years, PT 3-4 years; (3) Brunei Darussalam has a grand design with patterns: (A 7-3-2-2); 7-year elementary school, 3-year middle school, 2-year high school, 2-year pre-university; and (4) Southern Thailand (Patani) has a grand design with patterns: 6- (3-3); MI 6 years, MM 3 years, and MTs 3 years.